2010
DOI: 10.1016/j.arth.2009.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties, Oxidation, and Clinical Performance of Retrieved Highly Cross-Linked Crossfire Liners After Intermediate-Term Implantation

Abstract: Sixty Crossfire (Stryker Orthopaedics, Mahwah, NJ) liners were consecutively revised after an average of 2.9 years (range: 0.01 – 8.0 years) for reasons unrelated to wear or mechanical performance of the polyethylene. Femoral head penetration was measured directly from 42 retrievals implanted for over 1 year. Penetration rate results (0.04 mm/y, on average; range: 0.00-0.13 mm/y) confirmed decreasing wear rates with longer in vivo times. Overall, we observed oxidation levels at the bearing surface of the 60 li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
57
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 24 publications
4
57
1
Order By: Relevance
“…Previous studies have reported lower oxidation of the bearing surface for annealed and gamma inert sterilized highly crosslinked liners [7,18] as compared with the rim and may explain the general preservation of wear properties seen in clinical studies [9,18,28]. However, in the case of a malfunctioning hip such as chronic instability with dislocation, rim oxidation may contribute to localized delamination or rim fracture [18]. Previous studies of remelted liners, including shortterm retrievals, demonstrated low levels of oxidation [5,30].…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Previous studies have reported lower oxidation of the bearing surface for annealed and gamma inert sterilized highly crosslinked liners [7,18] as compared with the rim and may explain the general preservation of wear properties seen in clinical studies [9,18,28]. However, in the case of a malfunctioning hip such as chronic instability with dislocation, rim oxidation may contribute to localized delamination or rim fracture [18]. Previous studies of remelted liners, including shortterm retrievals, demonstrated low levels of oxidation [5,30].…”
Section: Introductionmentioning
confidence: 96%
“…Many clinical studies of firstgeneration highly crosslinked polyethylenes have reported superior wear performance of both annealed and remelted materials in the first decade of use [4, 9-14, 16, 24, 28] when compared with controls. Comparatively few studies have explored their long-term oxidative stability in vivo [8,18,20,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The free radicals were reduced by annealing but this implant was also terminally gamma sterilised, which introduced additional free radicals. In the long-term, there was significant oxidation in irradiated and annealed UHMWPE in vivo [21,35,72]. Despite this at intermediate follow-up (up to eight years), the penetration rates of highly crosslinked annealed UHMWPE are less than those for conventional UHMWPE [43,64], and the clinical effects of this elevated oxidation have yet to manifest themselves [35].…”
Section: Introductionmentioning
confidence: 99%
“…In the long-term, there was significant oxidation in irradiated and annealed UHMWPE in vivo [21,35,72]. Despite this at intermediate follow-up (up to eight years), the penetration rates of highly crosslinked annealed UHMWPE are less than those for conventional UHMWPE [43,64], and the clinical effects of this elevated oxidation have yet to manifest themselves [35]. One study showed fatigue damage at the oxidised rim of explanted irradiated and annealed UHMWPE acetabular liners although none were revised due to rim damage [21].…”
Section: Introductionmentioning
confidence: 99%